The New Cybersecurity Agenda : Economic and Social Challenges to a Secure Internet - Bauer, Johannes M.; Dutton, William H. (World Bank, Washington, DC, 2016)
This paper focuses on key economic and social factors underpinning worldwide issues around cybersecurity and, identifies a new agenda for addressing these issues that is being shaped by the Internet and related information and communication technologies, such as social media. All actors in the widening ecology of the Internet require a better social and cultural understanding of cybersecurity issues in order to effectively engage all relevant stakeholders in processes aimed at enhancing cybersecurity. The problems tied to cybersecurity are not new, but as the Internet becomes ever more essential to everyday life and work, and empowers users as never before, there are new social and economic aspects of the challenges to achieving a secure, open and global Internet that require much more focused attention. For years, computer scientists and engineers have recognized that cybersecurity is not merely an engineering and computer science problem, but also an economic and behavioral challenge. But recognition of the fact that cybersecurity cannot be successfully addressed with technical solutions alone, is not sufficient. It is critical that economists and other social and behavioral scientists engage in this area and address the practices of a wider range of actors in local and global arenas who need strategies that provide feasible and practical steps for securing the Internet and the incentives and mindsets to take them.